Ambientes virtuais: educação e cultura na construção do museu virtual josé américo de almeida - Petrucci, Mabel Ribeiro (2010)
This dissertation has as the subject-matter Virtual Environment: Education and Culture in the construction of the Virtual Museum José Américo de Almeida, and as objects of study, the Museum house José Américo de Almeida. We want to show the importance of the virtual environment as an element in a culture that takes into account the links between education and technology, focusing on the permanent institutional place in the service of society, characterized by decentralized knowledge, symbolic, participatory and personal motivation. With a view to monitor the new horizons of knowledge required by modern technological society, we had like main objectives, to analyze the principles of construction of the Virtual Museum José Américo de Almeida, seeking to understand the links between Education, Culture and Digital Technology, Information and Communication (TDIC), taking into account the approaches to identity, culture, media, multiculturalism, and thus the virtual environments. From these approaches in virtual environments, museums can be more "manipulated" by users interested in researching an icon of the Northeast culture, José Américo de Almeida, which may interact with the information available in the virtual environment. Therefore, this touches the construction of virtual museum of the importance of history, memory, cultural heritage,preservation of identity and the strengthening of culture. To conduct the research, we use references as a theoretical and methodological framework for qualitative research in the form of case study, based on the description of the construction of the Virtual Museum José Américo de Almeida - Expression of the Northeast culture. Therefore, it is also descriptive because it is a study in which the principal investigator is part of the construction that is the subject of study, we can say that it is a participatory research. In final considerations, we show that now, the virtual museum enables the interactivity of the Internet and its immediate mechanisms and simulating mediation between the public and museum object.